A new genus and species of Australian pergid sawfly (Hymenoptera: Symphyta, Pergidae) causing damage on grass (Poaceae) - Schmidt, Stefan; Brown, Graham (Zootaxa, 2005)
Dalia graminis, new genus and species, is described from the Darwin area in the Northern Territory, Australia. The new species belongs to the subfamily Euryinae and is most closely related to the genera Clarissa and Diphamorphos. Dalia graminis sp. nov. is the first record of an Australian pergid sawfly feeding on grass (Poaceae) causing severe damage on economically important crops.